Investigating the use of LEGO® Bricks in education and training: A systematic literature review (Journal of Applied Learning and Teaching, 2021)
Despite the increasing attention paid to LEGO® as a learning tool rather than a child’s toy, teaching practices and methodologies for using LEGO® vary according to educational contexts. The purpose of this paper was to investigate the various educational contexts of LEGO® usage in higher education and to identify trends in teaching practices. A systematic literature review was conducted on the use of LEGO® bricks in education and training using an exploratory sampling approach. A total of 298 articles were explored in internationally recognized journal databases using keyword search, and 26 articles were selected for a detailed review. We found a clear distinction in LEGO® usage between learning facilitation and thinking facilitation, as well as between individual application and group application. A simple typology with four quadrants is proposed based on our findings to help novice educators introduce LEGO® into their pedagogical designs.